Low Power and Low Area Junction-less Tunnel FET Design - Ragavendran, U; Ramachandran, M; ., . (International Journal of Engineering and Technology, 2018)
We present Junction less Tunnel FET with Si:SiGe, Si:AlGaAs and Si:InGaAsP and investigate their DC characteristics. The proposed structures present tremendous performance at a very low supply voltage. The key idea is to study device performance, which can be exploited as a digital switching device for 22 nm technology. Comparison of different heterostructures numerical simulations indicates that ION increases from 0.0024345 to 0.006532 A/Î¼m, when Si:SiGe is replaced with Si:InGaAsP for 22nm channel with supply voltage of 0.5V at a temperature of 300K.Â